2019
DOI: 10.1101/854000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Molecular Basis of Specific DNA Binding by the BRG1 AT-hook and Bromodomain

Abstract: AbstractThe ATP-dependent BAF chromatin remodeling complex plays a critical role in gene regulation by modulating chromatin architecture, and is frequently mutated in cancer. Indeed, subunits of the BAF complex are found to be mutated in >20% of human tumors. The mechanism by which BAF properly navigates chromatin is not fully understood, but is thought to involve a multivalent network of histone and DNA contacts. We previously identified a composite domain in the BRG1 ATPas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…This may suggest that it is largely the overall charge, rather than sidechain-specific protein-DNA contacts, that is conserved. Notably, two Y residues in the ZA-loop, one of which we previously observed to form interactions in the major groove of DNA, 20 do show conservation.…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…This may suggest that it is largely the overall charge, rather than sidechain-specific protein-DNA contacts, that is conserved. Notably, two Y residues in the ZA-loop, one of which we previously observed to form interactions in the major groove of DNA, 20 do show conservation.…”
Section: Resultsmentioning
confidence: 69%
“…We had previously found that the BRG1 AT-hook and BD span the minor and major grooves in binding to AT-rich DNA. 20 Our computational model of the complex suggested that a turn in the polypeptide at a linker proline (the C-terminal P of the PNPP element) is important for adopting this conformation. Here we find that the full PNPP element is important for promoting the conformation of the AT-L-BD in both the apo and DNA-bound states, and indeed all three prolines in the PNPP element of the linker are seen to be mutated in cancers.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations